"Estudio de quitosano extraído a partir de dos crustáceos camarón blanco (Litoprnacus setiferus) y camarón cebra (Rimapenaesus faoe) y su aplicación como clarificante en la industria licorera" - Espinales Terán, Johana Lilibeth (2020)
In this research work the extraction of chitosan obtained from shrimp shells is studied: white shrimp (Litopenaeus setiferus) and zebra shrimp (Rimapenaeus faoe) and its application as a clarifier, for this the objective was formulated: Extract chitosan from the shrimp shells by two extraction methods; chemical and hindu method. A completely randomized block experimental design with AxB factorial arrangement and four repetitions was used, for the extraction of chitosan, the following factors were used; Factor A (types of crustaceans) and Factor B (extraction methods). And an experimental design AxBxC and two repetitions to compare the clarification of the wines with the following factors: Factor A (type of chitosan), Factor B (fruit wine) and Factor C (% chitosan). The data analysis was carried out using the statistical package STATGRAPHICS, to define parameters various analyzes were carried out such as: pH, humidity, ash, ° Brix, acidity, density, alcohol degrees, turbidity, absorbance and methanol. In the analyzes, a pH of 7.13 to 7.95, ash from 0.304 to 0.478%, humidity from 10.13 to 15.99% with respect to chitosan was obtained. Strawberry and peach wines were also evaluated after clarification with chitosan, obtaining as results; pH 3.32 to 3.49, ° Brix 6 to 14.2, alcohol degrees 0.1 to 6.3, turbidity 0.184 to 5.055 NTU, absorbance 0.068 to 0.082 nm, with a yellow wavelength of 420 nm, the feasibility of extracting chitosan by the Indian method from white shrimp for clarification in fruit wine can be concluded, with the data obtained from this research based on the INEN 341 standard for alcoholic beverages and it is recommended to follow the working techniques in the Indian method to extract the chitosan required for clarification. Keywords: Shells, shrimp, extraction, chitosan, clarification, fruit wine.